The next generation : Jewish children and adolescents - Keysar, Ariela, 1955- (SUNY series in American Jewish society in the 1990s., 2000)
Drawing on the 1990 National Jewish population survey, this book questions the future of the Jewish Community's next generation and looks at demographic projections for the younger Jewish population.